2021
DOI: 10.3390/app11156991
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting of Antimicrobial Peptides from Insect (Hermetia illucens) and Its Applications in the Food Packaging

Abstract: About one-third of the total food produced is wasted, rising the concern to adopt proper management. Simultaneously with the increase in population, demand for food is increasing which may lead to scarcity. Adequate packaging is one of the ways to avoid deterioration of food and prevent wastage. In recent years, active packaging has attained interest due to its commendable results in food preservation. Several studies proved that the embodiment of antimicrobial components into the packaging material has the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 101 publications
0
19
0
Order By: Relevance
“…Food packaging plays a critical role in food supply chain and preserving the quality of food (Kumar et al 2021b ). Evolution in food packaging research has led to the exploration of innovative active packaging developed by incorporation of bioactive components, antimicrobial peptides, metal–organic frameworks (MOFs), and many more to achieve desired active packaging (Jafarzadeh et al 2020 ; Sultana et al 2021 ; Sharanyakanth and Radhakrishnan 2020 ). The paper aims to summarize the application of metal–organic frameworks in the food packaging sector.…”
Section: Introductionmentioning
confidence: 99%
“…Food packaging plays a critical role in food supply chain and preserving the quality of food (Kumar et al 2021b ). Evolution in food packaging research has led to the exploration of innovative active packaging developed by incorporation of bioactive components, antimicrobial peptides, metal–organic frameworks (MOFs), and many more to achieve desired active packaging (Jafarzadeh et al 2020 ; Sultana et al 2021 ; Sharanyakanth and Radhakrishnan 2020 ). The paper aims to summarize the application of metal–organic frameworks in the food packaging sector.…”
Section: Introductionmentioning
confidence: 99%
“…As an ecological decomposer, the BSF larvae are often present in areas where they are in close contact with zoonotic pathogenic microorganisms, such as bacteria and fungi, from the larva to adult stages [34,35]. BSF larvae can survive well in these environments owing to competing with bacteria for nutrients or inhibiting them [13].…”
Section: Discussionmentioning
confidence: 99%
“…BSF larvae have sole properties that can be employed for various defense purposes and contain a range of AMPs as potent inhibitory substances against different zoonotic pathogens [2]. Furthermore, previous studies have indicated a close correlation between the resistance of the BSF larvae to zoonotic pathogens and the antimicrobial substances produced by the larvae [11,24,34]. However, additional studies are needed to explore the antimicrobial substance derived from the BSF larvae.…”
Section: Discussionmentioning
confidence: 99%
“… Cecropin-like peptide 1 (CLP1) Hemolymph of immunized H. illucens larvae S. aureus (KCCM 40881, KCCM 12256) MNFTKLFVVFAVVLVAFAGQSEAGWRKRVFKPVEKFGQRVRDAGVQGIAIAQQGANVLATARGGPPQQG Fast protein liquid chromatography (FLPC), high-performance liquid chromatography (HPLC), matrix-assisted laser desorption/ionization-time-of-flight (MALDI-TOF) mass spectrometry (MS), RT–PCR Escherichia coli KCCM 11234 0.52 to 1.03 μmol/L AMP gene expression was increased in the muscle and trachea. Sultana et al. (2021) , Park and Yoe (2017a) Enterobacter aerogens KCCM 12177 1.03 to 2.07 μmol/L Pseudomonas aeruginosa KCCM 11328 1.03 to 2.07 μmol/L MRSA KCCM 40881 ND Staphylococcus aureus KCCM 12256 ND S. epidermidis ND Cecropin-like peptide 2 (CLP2) Hemolymph of immunized H. illucens larvae MNFAKLFVVFAIVLVAFSGQSEAGWWKRVFKPVEKLGQRVRDAGIQGLEIAQQGANVLATARGGPPQQG FLPC, HPLC, MALDI-TOF, MS, RT–PCR E. coli Park and Yoe (2017a) MRSA Cecropin-like peptide 3 (CLP3) MNFTKLFVVFAVVLIAFSGQSEAGWWKRVFKPVERLGQRVRDAGIQGLEIAQQGANVLATVRGGPPQQG Enterobacter aerogenes P. aeruginosa CecropinZ1 Crushed H. illucens larvae immunized with S. aureus and E. coli GWLKKIGKMKFILGTTLAIVIAIFGQCQAATWSYNPNGGATVTWTANVAATAR 3D structures of the AMP genes; protein expression, antimicrobial activity assay E. coli 15 to 30 μg/mL Elhag et al.…”
Section: Insects In Poultry Nutritionmentioning
confidence: 99%
“…(2020) E. coli KCCM 11234 Salmonella pullorum KVCC-BA0702509 S. typhimurium KCCM 40406 S. enteritidis KCCM 12021 H. illucens attacin (HI-attacin) Immunized H. illucens larvae with E. coli ; fat body, muscle, fore-gut, mid-gut, hind-gut, Malpighian tubule, and trachea samples MASKFLGNPNHNIGGGVFAAGNTRSNTPSLGAFGTLNLKDHSLGVSHTITPGVSDTFSQNARLNILKTPDHRVDANVFNSHTRLNNGFAFDKRGGSLDYTHRAGHGLSLGASHIPKFGTTAELTGKANLWRSPSGLSTFDLTGSASRTFGGPMAGRNNFGAGLGFSHRF E. coli KCCM 11234 HI-attacin transcripts levels a 27.5-fold increased in the fat body, a 4-fold increase in fore-gut, a 10.2-fold increase in muscle, and a 3.7-fold increase in the trachea comparing to control Shin and Park (2019) S. aureus KCCM 40881 MRSA Sarcotoxin 1, 2a, 2b, and 3 Crushed H. illucens larvae immunized with S. aureus , and E. coli Sarcotoxin 1: GWLKRKIGMKFILGTTLAIVVAIFGQCQAATWSYNPNGGATVTWTANVAATAR Sarcotoxin 2a: GWLKRKIGKKFILGTTLAIVVAIFGQCQAATWSYNPNGGATVTWTANVAATAR Sarcotoxin 2b: GWLKRKIGKKFILGTTLAIAVAIFGQCQAATWSYNPNGGATVTWTANVAATAR Sarcotoxin 3: GWLKRKIGMMMKNSNFNSTEEREAAKKNYKRKYVPWFSGANVAATAR Analysis of gene and 3D structures S. aureus , and E. coli; Four isoforms were detected for sarcotoxin: sarcotoxin 1, sarcotoxin (2a), sarcotoxin (2b), and sarcotoxin 3 Elhag et al. (2017) StomoxynZH1 Crushed H. illucens larvae immunized with S. aureus , and E. coli RGFRKHFNNLPICVEGLAGDIGSILLGVG 3D structures of the AMP genes; protein expression, antimicrobial activity assay E. coli 15 to 30 μg/mL Sultana et al. (2021) Elhag et al.…”
Section: Insects In Poultry Nutritionmentioning
confidence: 99%